Aster glehni Extract Containing Caffeoylquinic Compounds Protects Human Keratinocytes through the TRPV4-PPARδ-AMPK Pathway. (9th December 2018) - Lee, Yong-Jik; Jang, Yoo-Na; Han, Yoon-Mi; Kim, Hyun-Min; Jin, Changbae; Kim, Hyoung Ja; Seo, Hong Seog
Abstract : Aster glehni (AG) has been used in cooking and as a medicine to treat various diseases for over hundreds of years in Korea. To speculate the protective effects of AG on skin barrier, we estimated the protein levels of biomarkers related to skin barrier protection in human keratinocytes, HaCaT cells treated with sodium dodecyl sulfate (SDS), or 2, 4-dinitrochlorobenzene (DNCB). The protein levels for keratin, involucrin, defensin, tumor necrosis factor alpha (TNF α ), peroxisome proliferator-activated receptor delta (PPAR δ ), 5′ adenosine monophosphate-activated protein kinase (AMPK), serine palmitoyltransferase long chain base subunit 2 (SPTLC2), and transient receptor potential cation channel subfamily V member 4 (TRPV4) were evaluated using western blotting or immunocytochemistry in HaCaT cells. AG extract increased the protein levels of PPAR δ, phosphorylated AMPK, SPTLC2, keratin, involucrin, and defensin compared to the SDS or DNCB control group. However, TNF α expression increased by SDS or DNCB was decreased with AG extract. The order of action of each regulatory biomarker in AG pathway was identified TRPV4→PPAR δ →AMPK from antagonist and siRNA treatment studies. AG can ameliorate the injury of keratinocytes caused by SDS or DNCB through the sequential regulation of TRPV4→PPAR δ →AMPK pathway.